National profile on substance use, substance use‐related problems and policy: The case of Chile. - Castillo‐Carniglia, Alvaro (Addiction, 2025)
Aim: To provide a comprehensive overview of substance use, related problems, and policy responses in Chile, highlighting epidemiological trends, institutional contexts, and research findings. Methods: Narrative review of policy documents, published government and academic research, and primary analysis of national drug surveys and administrative data. It estimates trends in substance use prevalence, analyzes the regulatory landscape for tobacco, alcohol, and other drugs, and syntheses the current state of substance use research in Chile. Results: Chile exhibits a high prevalence of substance use, particularly for alcohol and cannabis, compared with other South American countries. Tobacco use has declined since the early 2000s, while alcohol use has remained stable. Cannabis use increased significantly between 2010 and 2016, reaching the highest prevalence in Latin America, but has since declined. While opioids and injecting substances are rare, alcohol and cocaine base paste are responsible for the largest health burden, representing 70% of all publicly funded treatments. Chile has approved and implemented various policy measures, including restrictions on alcohol sales and advertising, smoke‐free legislation, and reforms to drug laws that include home cultivation of cannabis for medical purposes. Research on substance use in Chile has increased in recent years, with only a few studies focusing specifically on policy evaluation. Conclusion: Although Chile has made progress in implementing evidence‐based substance use policies and expanding treatment services, substantial policy evaluation and enforcement gaps remain.